Trabecular architecture of the capitate and third metacarpal through ontogeny in chimpanzees (Pan troglodytes) and gorillas (Gorilla gorilla). Issue 138 (January 2020) - Ragni, Anna J.
Abstract: Chimpanzees ( Pan troglodytes ) and gorillas ( Gorilla gorilla ) both knuckle-walk in adulthood but are known to develop their locomotor strategies differently. Using dentally defined age-groups of both Pan and Gorilla and behavioral data from the literature, this study presents an internal trabecular bone approach to better understand the morphological ontogeny of knuckle-walking in these taxa. Capitate and third metacarpal bones were scanned by μCT at 23–43 μm resolution with scaled volumes of interest placed centrally within the head of the capitate and base of the third metacarpal. Trabecular measures related to activity level (size-adjusted bone volume/total volume, trabecular number, and bone surface area/bone volume) met expectations of decreasing through ontogeny in both taxa. Degree of anisotropy did not show statistical support for predicted species differences, but this may be due to the sample size as observed changes through ontogeny reflect expected trends in the capitate. Analyses of principal trabecular orientation corroborated known behavioral differences related to variation of hand use in these taxa, but only Pan showed directional patterning associated with suggested wrist posture. Assessment of allometry showed that the trabecular bone of larger animals is characterized by fewer and thinner trabeculae relative to bone size. In combination, these findings confirm the efficacy of trabecular bone in reflecting locomotor ontogeny differences between closely related taxa. These techniques show promise for use within the hominin fossil record, particularly for taxa hypothesized to be arboreal in some capacity.